Agreement between telehealth and in-person assessment of patients with chronic musculoskeletal conditions presenting to an advanced-practice physiotherapy screening clinic. (December 2018) - Cottrell, Michelle A.; O'Leary, Shaun P.; Swete-Kelly, Patrick; Elwell, Bula; Hess, Sally; Litchfield, Mary-Ann; McLoughlin, Ian; Tweedy, Rebecca; Raymer, Maree; Hill, Anne J.; Russell, Trevor G.
Abstract: Objective: To determine the level of agreement between a telehealth and in-person assessment of a representative sample of patients with chronic musculoskeletal conditions referred to an advanced-practice physiotherapy screening clinic. Design: Repeated-measures study design. Participants: 42 patients referred to the Neurosurgical & Orthopaedic Physiotherapy Screening Clinic (Queensland, Australia) for assessment of their chronic lumbar spine, knee or shoulder condition. Intervention: Participants underwent two consecutive assessments by different physiotherapists within a single clinic session. In-person assessments were conducted as per standard clinical practice. Telehealth assessments took place remotely via videoconferencing. Six Musculoskeletal Physiotherapists were paired together to perform both assessment types. Main outcome measures: Clinical management decisions including (i) recommended management pathways, (ii) referral to allied health professions, (iii) clinical diagnostics, and (iv) requirement for further investigations were compared using reliability and agreement statistics. Results: There was substantial agreement (83.3%; 35/42 cases) between in-person and telehealth assessments for recommended management pathways. Moderate to near perfect agreement (AC1 = 0.58–0.9) was reached for referral to individual allied health professionals. Diagnostic agreement was 83.3% between the two delivery mediums, whilst there was substantial agreement (81%; AC1 = 0.74) when requesting further investigations. Overall, participants were satisfied with the telehealth assessment. Conclusion: There is a high level of agreement between telehealth and in-person assessments with respect to clinical management decisions and diagnosis of patients with chronic musculoskeletal conditions managed in an advanced-practice physiotherapy screening clinic. Telehealth can be considered as a viable and effective medium to assess those patients who are unable to attend these services in person. Highlights: Many patients unable to access advance-practice physiotherapy screening clinics. Agreement between in-person and telehealth MSK physiotherapy assessment evaluated. 42 patients with low back, knee or shoulder condition recruited from waitlists. Substantial agreement between two mediums demonstrated for clinical decisions. Telehealth is viable medium to assess patients unable to access service in person.